Ketogenic diet in psychiatry: application in treating depression among athletes - Paulina Kumięga; Zuzanna Kudas; Nikola Perchel; Aleksandra Litwin; Karolina Krzywicka; Paweł Nowocin; Piotr Wasiński; Natalia Dąbrowska; Martyna Koszyk; Dawid Kulczyński (Quality in Sport)
Depression is a prevalent mental health challenge, particularly in athletes, where the interplay of high-performance demands, physical stress, and injury exacerbates psychological vulnerabilities. Emerging evidence suggests that the ketogenic diet (KD), a high-fat, moderate-protein, and low-carbohydrate dietary intervention, holds therapeutic potential for managing depression. KD induces ketosis, a metabolic state that enhances brain energy metabolism, reduces neuroinflammation, and stabilizes neurotransmitter function, all of which are implicated in the pathophysiology of depression.